2021
DOI: 10.3389/fpsyg.2020.631994
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and Burnout During the COVID-19 Crisis: A Two-Wave Cross-Lagged Study

Abstract: The current study aims at examining the relationship between the perfectionism two-factor model (i.e., concerns and strivings) and burnout dimensions measured by using the BAT (Burnout Assessment Tool) through a longitudinal study. A two-wave cross-lagged study was conducted using path analysis in SEM (Structural Equation Modeling) of 191 workers. Results confirmed the predictive role of perfectionistic concerns on the burnout dimensions, whereas perfectionistic strivings were not significantly related, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 46 publications
3
24
0
1
Order By: Relevance
“…The current findings are also consistent with diathesis-models of perfectionism and distress (Hewitt & Flett, 1991 ; 1993) and Flett and Hewitt’s ( 2020 ) contention that the stress of the pandemic would be particularly difficult for individuals elevated in perfectionism and would result in higher levels of psychological distress. Results are also consistent with a study on Italian adults, which found that trait perfectionism in the early stages of the pandemic predicted higher levels of psychological distress and burnout 2 months later (Spagnoli et al, 2021 ). These findings also dovetail with previous work showing robust links between perfectionism and anxiety pre-pandemic (Burgess & DiBartolo, 2016 ; Hewitt et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current findings are also consistent with diathesis-models of perfectionism and distress (Hewitt & Flett, 1991 ; 1993) and Flett and Hewitt’s ( 2020 ) contention that the stress of the pandemic would be particularly difficult for individuals elevated in perfectionism and would result in higher levels of psychological distress. Results are also consistent with a study on Italian adults, which found that trait perfectionism in the early stages of the pandemic predicted higher levels of psychological distress and burnout 2 months later (Spagnoli et al, 2021 ). These findings also dovetail with previous work showing robust links between perfectionism and anxiety pre-pandemic (Burgess & DiBartolo, 2016 ; Hewitt et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the current work was relegated to the early stages of the pandemic, thus precluding an investigation of longer-lasting changes. Interestingly, a study on adults found that trait perfectionism (i.e., perfectionistic concerns and strivings) did not change across a two-month interval early on in the pandemic (Spagnoli et al, 2021 ). However, given differences in samples (i.e., Canadian EAs versus Italian adults), measures of perfectionism (perfectionistic cognitions versus trait perfectionism), and time intervals (assessing pre-pandemic to during pandemic changes versus changes during the early stages of the pandemic) it is difficult to compare findings.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that these four dimensions relate to a higher-order construct of burnout (see Schaufeli et al, 2020aSchaufeli et al, , 2020bSpagnoli et al, 2021;Sakakibara et al, 2020;Hadibarjramovic et al, 2020). Notably, the BAT construct has a threshold cut-off representing very high burnout (Schaufeli et al, 2020a(Schaufeli et al, , 2020b or burnt-out.…”
Section: Bat Supporting Evidencementioning
confidence: 99%
“…Over the past year there has been a growing number of studies in which BAT was used to assess the onset of burnout symptoms (e.g., [57]). De Beer and colleagues [58] offered a comprehensive overview of the BAT across seven nations (i.e., Belgium, Netherlands, Austria, Germany, Finland, Ireland, and Japan).…”
Section: A New Complex Tool: the Batmentioning
confidence: 99%